Laws of the State of Maine; to Which are Prefixed the Constitution of the U. States and of Said State, in Two Volumes, with an Appendix Page 55, Image 126 (Vol. 1, 1821) § 7 - (:unkn) unknown (General Publisher, 1821)
Be it further enacted, That if any person shall voluntarily engage in a duel, with rapier, a small sword, back sword, pistol, or other dangerous weapon, to the hazard of life, when no homicide shall ensue thereon; and if any person shall, by word, message, or in any other manner, challenge another to fight in a duel, as aforesaid, when no duel shall be fought thereon, every such offender, and every person who shall be knowingly a second, agent or abettor in such duel or challenge, upon due conviction of either of said offences in the Supreme Judicial Court, shall be punished as a felonious assaulter;
--
Keywords: DUELING